Mapping Educational Participation: A Quadrant Analysis of Gross and Net Enrollment Rates (2020–2024) - Khofifah, Juliani Musti; Kurniatun, Taufani Chusnul; Asih, Sinta; Andini, Fania Sahwa (research, training and philanthropy institution Natural Aceh, 2025)
This study aims to analyze quadrant mapping of the Gross Enrollment Rate (GER) and Net Enrollment Rate (NER) towards measuring education participation in Aceh Province from 2020 to 2024. Descriptive quantitative approaches were applied throughout this research, where secondary data were obtained from education statistics by government agencies and national surveys. It applies the quadrant technique with four categories of education participation rates based on the national average net and gross enrollment rates. The results demonstrate that primary and junior secondary education belong to Quadrant I (ideal) since there is a consistently higher net and gross enrollment rate than the national average. In contrast, senior secondary education is situated on Quadrant II (non-ideal) with a high gross enrollment rate but a low net enrollment rate, indicating problems such as late enrollment or high dropout rates. The findings of this research confirm the imperative need for data-informed and context-specific education policies for autonomous regions such as Aceh to reduce the GER-NER differential. The strategy is vital for promoting inclusive, equitable, and sustainable education development aligned with national targets and the Sustainable Development Goals (SDGs).